Acceptorless and base-free dehydrogenation of alcohols and amines using ruthenium-hydride complexes - Muthaiah, Senthilkumar (2013)
An efficient, operatively simple, acceptorless, and base-free dehydrogenation of secondary alcohols and nitrogen-containing heterocyclic compounds was achieved by using readily available ruthenium hydride complexes as precatalysts. The complex RuH2(CO)(PPh3)3 (1) and Shvo’s complex (2) showed excellent activities for the dehydrogenation of secondary alcohols and nitrogen containing heterocycles. In addition to complexes 1 and 2, the complex RuH2(PPh3)4 (3) also showed moderate to excellent activity for the acceptorless dehydrogenation of nitrogen-containing heterocyclic compounds. Kinetic studies on the oxidation reaction of 1-phenylethanol using complex 1 were carried out in the presence and the absence of external triphenylphosphine (PPh3). External addition of PPh3 had a negative influence on the rate of the reaction, which suggested that dissociation of PPh3 occurred during the course of the reaction. Hydrogen was evolved from the oxidation reaction of 1-phenylethanol by using 1 mol% of 1 (88%) and 2 (92%), which demonstrated the possible usage of the catalytic systems in hydrogen generation.